A Comparative Study of Processing Speed by Gender in Learning Disabled and Non-Learning Disabled Student Populations - Jilsy P; Dr Mansi Kapoor (International Journal of Scientific Research in Science and Technology, 2025)
Processing speed is a core cognitive function that refers to the efficiency and rate at which individuals perceive, understand, and respond to information. Learning disability is a neurodevelopmental condition characterized by persistent difficulties in acquiring and using academic skills despite adequate intelligence and educational opportunities. The present study aimed to compare processing speed by gender among learning disabled (LD) and non-learning disabled (NLD) student populations. The study was conducted among school-going children aged 8–12 years from Kerala, India. A total sample of 300 students was selected using purposive sampling, comprising 150 students with learning disabilities (75 males and 75 females) and 150 students without learning disabilities (75 males and 75 females). Processing speed was assessed using the Processing Speed Index subtests—Coding and Symbol Search—of the Wechsler Intelligence Scale for Children (WISC). The collected data were analyzed using Statistical Package for the Social Sciences (SPSS) version 28. The hypothesis stated that there would be a significant gender difference in processing speed among children with and without learning disabilities. Appropriate inferential statistical tests were employed to examine group and gender differences. The results revealed a statistically significant gender difference in processing speed across both LD and NLD groups, thereby supporting the stated hypothesis. The findings highlight the role of gender in processing speed performance and underscore the importance of considering cognitive processing differences in educational assessment and intervention planning for children with learning disabilities.
Keywords: Processing speed; learning disability